Validity evaluation of ScxAl1−xN material constants based on SAW characteristics. (28th September 2016) - Tang, Gongbin; Han, Tao; Zhang, Qiaozhen; Yamazaki, Kenta; Omori, Tatsuya; Hashimoto, Ken-ya
Abstract: This paper is aimed at examining the validity of material constants reported for use in surface acoustic wave (SAW) device simulations. First, based on the full set of material constants calculated by first principle, bulk acoustic wave velocities are calculated for Sc x Al1− x N and compared with published experimental results. Then, the effects of the Sc x Al1− x N material constants with different Sc content on acoustic characteristics are calculated and the influence of shear vibrations on SAW characteristics are recognized. Then, a series of SAW devices are fabricated on Sc x Al1− x N film/Si substrate structure with various Cu and ScAlN thicknesses h Cu and h ScAlN, respectively, and measured variations of phase velocity V and effective electromechanical coupling factor K e 2 with these parameters are compared with the calculation. The fairly well-agreed results indicate a reliable set of Sc x Al1− x N material constants for SAW device simulations.